ANALYSIS OF THE COMMUNITY-BASED EMPOWERMENT PROCESS IN MANGROVE ECOTOURISM MANAGEMENT IN TELUK SEMANTING TOURISM VILLAGE - Faathihsia Ridda Aulya Kur'aeny; Mustangin; Wahdatan Nisa; Muhamad Alisalman (SOSIOEDUKASI, 2025)
This study aims to analyze the process of community empowerment in the management of community-based mangrove ecotourism in Teluk Semanting Tourism Village, Berau Regency. This study uses a qualitative approach with a case study design, referring to seven stages of empowerment, namely: preparation, review, alternative program planning, performance of action plans, implementation, evaluation, and termination. Data was obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The results of the study show that empowerment is carried out in stages and participatory, resulting in strengthening local institutions, increasing the capacity of MSMEs (micro, small and medium enterprises) processed marine and mangrove products, and growing ecological awareness of the community. The termination process also indicates an increase in community independence in managing ecotourism in a sustainable manner